Analysis of the Effect of Profitability, Liquidity, Leverage, and Firm Size on Financial Distress During Pandemic COVID-19 - Barus, Romaya Anjali Br; Ida Adhani (ADPEBI, 2022)
Abstract The purpose of this study was to determine the effect of Profitability (ROA), Liquidity (CR), Leverage (DER), and Firm size on Financial Distress in Telecommunication Sector Companies Listed in BEI for the 2019-2021 period during the Pandemic COVID-19. The data used in this research is secondary data with a purposive sampling technique. Where there are 4 companies as a sample from a population of 6 telecommunications companies. The research method used is multiple linear regression with classical assumption test prerequisites, followed by partial significance by using the hypothesis test, namely the T-test while finding out simultaneously using the F test with a significance level of 5%. This study shows partial results (T-test) by obtaining the results that Profitability (ROA) has a negative and significant effect on Financial Distress, Liquidity (CR) has a negative and significant effect on Financial Distress, Leverage (DER) has a positive and significant effect on Financial Distress, and Firm size has no effect on Financial Distress. And for the simultaneous research results (F test) show the results of Profitability (ROA), Liquidity (CR), Leverage (DER), and Firm Size jointly affect Financial Distress. In addition, the predictive ability of the three independent variables on accounting conservatism can be seen from the coefficient of determination of 95.6% while the remaining 4.4% is explained by other variables that are not examined outside the research model. Keywords: Profitability (ROA), Liquidity (CR), Leverage (DER), Firm Size, and Financial Distress.